Sympatric species of Heilipus Germar (Coleoptera: Curculionidae: Hylobiini) on fruits of Lauraceae: a new species from Brazil and redescription of Heilipus draco (Fabricius, 1801) - Sanz-Veiga, Priscila A.; Leivas, Fernando W. T.; Díaz-Grisales, Valentina; Anzaldo, Salvatore; Rosado-Neto, Germano H.; Lampert, Silvana; Maggio, Daniela H.; Corrêa, Alberto S.; Savaris, Marcoandre (Zootaxa, 2024)
The genus Heilipus Germar (Curculionidae: Hylobiini) is an American weevil group with 89 described species, of which 28 species are known from Brazil. Here, we describe a new species of Heilipus from Brazil and redescribe H. draco (Fabricius, 1801). Heilipus vividaensis Sanz-Veiga, Savaris & Leivas, sp. nov. and H. draco are similar sympatric species, reared from fruits of Ocotea puberula (Rich.) Nees and Nectandra angustifolia (Schrad.) Nees & Mart. (Lauraceae) in south and southeast Brazil. External morphological and genitalia descriptions, illustrations, distribution records, notes on the host plant, and a barcode DNA sequence are provided for both species.